Badania strategii małych przedsiębiorstw rodzinnych w Polsce - Marjański, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The character of strategies of small family enterprises is determined by the influence of family factors and the limited size and resources of the subject. Because of the specific character of family companies, in the process of construction and strategy implementation, not only rational principles and willingness to maximize profits are of great importance, but also family interest, its norm and values. The strategic planning has parallel character integrating both family and business goals. The crucial long-term element of the strategy is an inheritance and desire for assuring functioning of the company through generations coming one after another. Methods of strategic analysis encounter difficulties at limited application and strategies have unformalized, incremental and emergent character. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 248-257